Kajian Agroekologi terhadap Strategi Pemenuhan Kebutuhan Pangan Masyarakat di Kabupaten Belu Nusa Tenggara Timur - Carolina, Carolina; Hidajat, Elok Wahju (JURNAL PANGAN, 2016)
A local agroecosystem is the main food source, especially corn, for the people of Belu, East Nusa Tenggara. Although poverty is in general still an obstacle to achieving food security, local farmers’ strategy in managing local resources to fulfill food needs is valuable to be explored to discover the prospect of local potency. A case study is conducted in Bakustulama Village in West Tasifeto, Belu Subdistrict for exploring the local wisdom. Data are collected using an agroecological approach that allows integration of ecology, economy and social elements in food system perspective in lieu with food security definition to include food availability, accessibility, and continuity. It is found that food security strategy is performed through enabling agroecosystem to produce corn in multiple cropping systems, combining corn as a carbohydrate source, beans as a protein source, and other plant species rich in vitamin and minerals with good exchange value. Co-management principal is used from preparing land until harvesting. Corn is then stored to assure yearlong supply. As a staple food, corn is prepared traditionally as jagung ketemak and jagung bose, or mixed with rice. Based on the typical corn agroecosystem management, it is concluded that by means of appropriate technology introduction in cultivation system and post-harvest, significant value add could be acquired to improve not only food availability but also its accessibility.